From Sound to Speech: How Interactive Speaking Shapes Pronunciation Skills - Dinar Dipta; Dian Nashrul Munif; Hanifa Maisaroh (Lingual: Journal of Language and Culture, 2025)
Interactive speaking skills encompass abilities such as agreeing, disagreeing, expressing opinions, clarifying statements, responding to challenges, offering suggestions, reinforcing ideas, and providing accurate information. However, a preliminary study revealed a lack of interactive engagement during English lessons, leading to minimal student participation. This research examines how teachers utilize interactive speaking strategies for effective pronunciation instruction and evaluates students’ pronunciation skills. Conducted as a qualitative case study with eighth-grade English teachers, data were collected through classroom observations, interviews, and documentation. The analysis was descriptive, with results presented in narrative form rather than numerical data. Triangulation methods helped verify the trustworthiness of the data. The findings indicate that, although the teacher assigns dialogue-based tasks aimed at promoting interaction, several key elements of interactive speaking theory are not implemented, limiting classroom interaction. This shortcoming diminishes the effectiveness of pronunciation teaching and negatively affects the overall quality of English language education.